Polyester resin composition and polyester film
The polyester resin composition with high naphthalene carboxylic acid and ethylene glycol content, combined with controlled polyalkylene glycol and alkaline metal compounds, addresses thermal and mechanical limitations of polyethylene naphthalate, enabling high-temperature and optical films with improved heat resistance and clarity.
Patent Information
- Application Number
- JP2020203879
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-09
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-12-09
AI Technical Summary
Existing polyethylene naphthalate compositions face limitations in high molten viscosity, high molecular weight, brittleness, and thermal breakdown, which affect their suitability for high-temperature applications and optical films.
A polyester resin composition with a high content of naphthalene carboxylic acid (95 mol% or more) and ethylene glycol (95 mol% or more), along with controlled amounts of polyalkylene glycol and alkaline metal compounds, to achieve low thermal degradation and improved heat resistance, refractive index control, and film formation.
The composition provides films with excellent heat resistance, controlled refractive index, and optical clarity, suitable for applications like liquid crystal displays and infrared reflective films, with minimal thermal degradation and bubble formation.
Smart Images

Figure 0007625838000001 
Figure 0007625838000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester resin composition and a polyester film. [Background technology]
[0002] Polyethylene naphthalate has excellent mechanical properties and heat resistance and is used for a variety of purposes.
[0003] However, polyethylene naphthalate has a high melt viscosity, and there is a limit to how much molecular weight can be increased by melt polymerization, and the resulting polymer is brittle. Therefore, various copolymer compositions are being investigated.
[0004] For example, Patent Document 1 discloses a technique for improving crystallinity by copolymerizing polyethylene glycol or polytetramethylene glycol, and in the examples, discloses polyethylene naphthalate copolymerized with polyethylene glycol or polytetramethylene glycol having a molecular weight of 1000 to 2000.
[0005] Furthermore, Patent Document 2 discloses polyethylene naphthalate copolymerized with 10 to 50% by weight of a hydrophilic compound, and in the examples, discloses polyethylene naphthalate copolymerized with polyethylene glycol having a molecular weight of 1,000 to 6,000.
[0006] However, these techniques are insufficient to suppress the thermal decomposition that is believed to be caused by polyalkylene glycol. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 8-48758 [Patent Document 2] JP 2013-87153 A Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a polyester resin composition having excellent heat resistance and suitable for biaxially oriented films, particularly laminated polyester films, and a film made using the same, that is, a laminated polyester film. [Means for solving the problem]
[0009] That is, the object of the present invention is to provide a polyester having aromatic dicarboxylic acid units and alkylene glycol units, the content of naphthalenedicarboxylic acid components being 95 mol % or more based on the total dicarboxylic acid components, the content of ethylene glycol components being 95 mol % or more based on the total diol components, and containing a polyalkylene glycol component, and the heat loss when heated at 300°C for 150 minutes in a nitrogen atmosphere is 0.3% by weight or less. This is achieved by a polyester resin composition having a glass transition temperature of 100° C. or higher and 110° C. or lower, and a crystallization temperature in a solid state of 200° C. or higher and 220° C. or lower, as measured by differential scanning calorimetry. Effect of the Invention
[0010] According to the present invention, it is possible to provide a polyester resin composition having excellent heat resistance, and further to provide a film, i.e., a laminated polyester film, made using the same. These films can be applied to optical applications such as liquid crystal displays, and in particular, by forming the multi-layer laminated polyester film with a controlled refractive index distribution, it can be used for applications such as a total light reflecting polyester film and a heat ray reflecting polyester film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The polyester resin composition of the present invention is a polyester having aromatic dicarboxylic acid units and alkylene glycol units, and is required to have a naphthalene dicarboxylic acid component content of 95 mol % or more relative to all dicarboxylic acid components, a ethylene glycol component content of 95 mol % or more relative to all diol components, and a polyalkylene glycol component.
[0012] In the polyester resin of the present invention, the content of the naphthalene dicarboxylic acid component must be 95 mol% or more, and more preferably 98 mol% or more, based on the total dicarboxylic acid components, in order to increase the refractive index. In addition, other dicarboxylic acid components can be used within a range of 5 mol% or less, and examples of such components include terephthalic acid components, isophthalic acid components, cyclohexanedicarboxylic acid components, decacarboxylic acid components, adipic acid components, and sebacic acid components. Among these, aromatic compounds such as terephthalic acid components, isophthalic acid components, cyclohexanedicarboxylic acid components, and decacarboxylic acid components, and alicyclic compounds are preferred in terms of increasing the refractive index and heat resistance.
[0013] The alkylene glycol component of the polyester resin composition of the present invention must contain 95 mol % or more of ethylene glycol based on the total diol component in terms of increasing the refractive index, crystallinity, melt viscosity, and film-forming properties. The polyester resin composition of the present invention must contain polyalkylene glycol, and from the viewpoints of heat resistance and film-forming properties, the content of polyalkylene glycol is preferably 4% by weight or more and 8% by weight or less relative to the polyester resin composition. If the content of polyalkylene glycol exceeds 8% by weight, decomposition gas due to decomposition products of polyalkylene glycol is generated, and air bubbles are generated in the film, which may cause optical defects. Examples of such polyalkylene glycol include polyethylene glycol and polytetramethylene glycol from the viewpoints of heat resistance and film formation, and polyethylene glycol is preferred from the viewpoints of design of glass transition temperature and heat resistance. Polyethylene glycol is prone to generate formaldehyde in thermal decomposition, but polytetramethylene glycol is concerned about generating a large amount of decomposition gas because the compound of the tetramethylene glycol unit, which is the decomposition product, generates tetrahydrofuran by intramolecular condensation. The number average molecular weight of polyethylene glycol is preferably 200 or more and 600 or less from the standpoints of reactivity and heat resistance.
[0014] The timing of addition of such polyalkylene glycol may be any stage from before the ester exchange reaction, which is a process for producing a polyester resin, to before the start of the polycondensation reaction. From the viewpoint of reactivity, however, it is preferable to add it before the ester exchange reaction.
[0015] In the polyester resin composition of the present invention, the alkali metal element content is preferably 10 ppm or more and 100 ppm or less based on the mass of the polyester resin composition from the viewpoint of heat resistance, and more preferably 80 ppm or less from the viewpoint of reducing foreign matter.
[0016] The heat loss of the present invention is required to be 0.3% by weight or less when heated at 300°C for 150 minutes under a nitrogen atmosphere, and more preferably 0.25% by weight or less. Specifically, using a Seiko Instruments Inc. TG / DTA6200, the temperature is raised from room temperature to 300°C at a rate of 20°C / min under a nitrogen atmosphere (50 ml / min), and the weight at the time of reaching 300°C is used as the reference, and the difference between the weight after 150 minutes at 300°C is calculated as the heat loss. The time of reaching 300°C is set as the zero point in order to cancel the influence of low boiling point oligomer components and moisture in the polyester resin composition, which are usually removed in the drying process. If the heat loss exceeds 0.3% by weight, the generation of formaldehyde caused by polyethylene glycol increases, which may cause the formaldehyde concentration around the T-die to increase or cause film defects due to the generation of bubbles.
[0017] The alkali metal element is preferably sodium or potassium from the viewpoints of heat resistance and reduction of foreign matter, and the compound is preferably a hydrate or anhydride of sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, etc. The alkali metal compound can be added at any stage from the start of the transesterification reaction to before the start of the polycondensation reaction, which is the production process of the polyester resin, but when added as an alkali metal phosphate compound, it is preferably added between the end of the transesterification reaction and before the start of the polycondensation reaction.
[0018] The glass transition temperature of the polyester resin composition of the present invention (midpoint glass transition temperature: the temperature at the point where a line equidistant in the vertical direction from the extended straight lines of each baseline intersects with the curve of the stepwise change portion of the glass transition) is preferably 100° C. or more and 110° C. or less from the viewpoint of film formability. Specifically, the glass transition temperature is the glass transition temperature when 10 mg of the polyester resin composition is melted at 300° C., held for 5 minutes, rapidly cooled to room temperature, and then heated at a heating rate of 16° C. / min.
[0019] From the viewpoint of heat resistance, the crystallization temperature in the solid state of the polyester resin composition of the present invention is preferably 200° C. or more and 220° C. or less. Specifically, 10 mg of the polyester resin composition is melted at 300° C., held for 5 minutes, rapidly cooled to room temperature, and then heated to 300° C. at a heating rate of 16° C. / min and held for 5 minutes. The sample is then temporarily removed, rapidly cooled to room temperature on an iron plate, and heated again at a rate of 16° C. / min. The peak temperature of the crystallization peak is the crystallization temperature.
[0020] The polyester resin composition of the present invention can be produced by a conventionally known method. A specific production example will be shown below, but the present invention is not limited thereto. 95.5 parts by weight of dimethyl naphthalenedicarboxylate, 47.6 parts by weight of ethylene glycol, and 6.3 parts by weight of polyethylene glycol (number average molecular weight 400) are charged into a reaction vessel and dissolved at 180° C., and then an ester exchange reaction catalyst is added with stirring.
[0021] The polyalkylene glycol may be added at any stage from before the ester exchange reaction to before the start of the polycondensation reaction. From the viewpoint of reactivity, however, it is preferably added before the ester exchange reaction.
[0022] As the transesterification reaction catalyst, a compound having a known transesterification ability, such as titanium alkoxide, titanium chelate compound, or a metal acetate such as manganese acetate, magnesium acetate, or calcium acetate, can be used. In the case of manganese acetate tetrahydrate, the reaction proceeds sufficiently when 0.05 to 0.06 parts by weight of the manganese acetate tetrahydrate is added as an ethylene glycol solution. After the addition of the transesterification catalyst, the temperature is raised to 240°C over 3 to 4 hours while distilling off the by-product methanol. The target for the completion of the transesterification reaction is preferably 90% or more of the theoretical amount (when 100% reaction occurs, twice the molar amount of methanol as dimethyl naphthalenedicarboxylate is generated). After the completion of the transesterification reaction, various phosphorus compounds as heat resistant stabilizers, antioxidants, antifoaming agents, etc. can be added.
[0023] Examples of phosphorus compounds include phosphoric acid, phosphorous acid, phosphonic acid, and phosphinic acid compounds, and known phosphorus compounds such as phosphoric acid, phosphorous acid, trimethylphosphate, and ethyl diethylphosphonoacetate can be used. In this case, it is preferable to use an alkali metal phosphate in combination in terms of improving heat resistance. The amount of such phosphorus compound to be added is 0.022 parts by weight of phosphoric acid and 0.026 parts by weight of sodium dihydrogen phosphate dihydrate per 100 parts by weight of the polyester resin composition, and the molar ratio of manganese element to phosphorus element is about 1.0, resulting in good heat resistance.
[0024] After the addition of additives such as phosphorus compounds is completed, the reaction product is transferred to a polycondensation apparatus, and a polycondensation catalyst is added. Known compounds can be used as the polycondensation catalyst, and examples of such compounds include titanium chelate compounds, titanium alkoxides, germanium dioxide, antimony trioxide, antimony acetate, and aluminum catalysts. In the case of antimony trioxide, an amount of about 0.015 parts by weight of the polycondensation catalyst is sufficient.
[0025] The alkali metal compound can be added at any stage between the start of the ester exchange reaction and before the start of the polycondensation reaction. When it is added as an alkali metal phosphate compound, it is preferably added between the end of the ester exchange reaction and before the start of the polycondensation reaction.
[0026] After adding the polycondensation catalyst, the pressure inside the device is reduced to 133 Pa or less, and the temperature is raised to 290°C over 3 to 4 hours. The polycondensation reaction is carried out while distilling off by-products. When the reactant reaches a specified viscosity, the reaction is stopped and the molten polyester is discharged into a water tank. The discharged polyester is quenched in the water tank and cut into chips with a cutter.
[0027] In this manner, a polyester resin composition can be obtained, but the above is merely an example, and the raw materials, catalysts, and polymerization conditions are not limited to those described above.
[0028] The polyester film of the present invention preferably contains 80% by weight or more of the polyester resin composition of the present invention from the viewpoints of heat resistance and optical properties. In the laminated polyester film of the present invention, at least one of the polyester resin layers constituting the laminated polyester film preferably contains 80% by weight or more of the polyester resin composition of the present invention, and the other polyester resin layer is preferably composed of an amorphous polyester resin. The layer containing 80% by weight or more of the polyester resin composition of the present invention can have a higher in-plane refractive index in the stretching and heat treatment process than that in the amorphous state before stretching. On the other hand, in the case of an amorphous polyester resin, by performing heat treatment at a temperature far exceeding the glass transition temperature in the heat treatment process, the slight orientation caused in the stretching process can be completely relaxed, and the low refractive index of the amorphous state can be maintained. In this way, a refractive index difference can be easily provided between the layer containing 80% by weight or more of the polyester resin composition of the present invention and the layer made of an amorphous polyester resin in the stretching and heat treatment processes in the production of the film.
[0029] Next, a preferred method for producing the laminated polyester film of the present invention will be described below using the polyester resin composition and the amorphous polyester resin of the present invention, but the method is not limited thereto. The laminated polyester film can be produced according to paragraphs
[0053] to
[0063] of JP-A-2007-307893.
[0030] In addition, when preparing a laminated polyester film made of a plurality of polyester resins, a plurality of resins such as the polyester resin composition of the present invention and the amorphous polyester resin are fed from different flow paths using two or more extruders and fed into a lamination device. As the lamination device, a multi-manifold die, a feed block, a static mixer, etc. can be used, but in particular, in order to efficiently obtain the configuration of the present invention, it is preferable to use a feed block that includes at least two or more separate members having a large number of fine slits. When such a feed block is used, the device does not become extremely large, so that there is little foreign matter due to thermal deterioration, and even if the number of layers is extremely large, high-precision lamination is possible. In addition, the lamination accuracy in the width direction is also significantly improved compared to the conventional technology. In addition, it is also possible to form an arbitrary layer thickness configuration. The laminated polyester film of the present invention is preferably a multi-layer laminated polyester film having 50 or more layers. It is preferably 100 layers or more, more preferably 200 layers or more, and preferably 3000 layers or less.
[0031] The molten multilayer laminate thus formed in the desired layer structure is guided to a die, extruded onto a cooling body such as a casting drum, and cooled and solidified to obtain a casting film. In this case, it is preferable to use a wire-shaped, tape-shaped, needle-shaped, or knife-shaped electrode to rapidly solidify the laminate by electrostatic force against a cooling body such as a casting drum. In addition, a method of blowing air from a slit-shaped, spot-shaped, or planar device to rapidly solidify the laminate by closely contacting the cooling body such as a casting drum, or a method of rapidly solidifying the laminate by closely contacting the cooling body with a nip roll, is also preferable. The casting film thus obtained is preferably biaxially stretched. Here, biaxial stretching refers to stretching in the longitudinal direction and the width direction. Stretching may be performed in two directions successively, or may be performed in two directions simultaneously. In addition, re-stretching may be performed in the longitudinal direction and / or the width direction.
[0032] First, the case of sequential biaxial stretching will be described. Here, stretching in the longitudinal direction refers to stretching for giving the film molecular orientation in the longitudinal direction, and is usually performed by the difference in peripheral speed of rolls. This stretching may be performed in one stage, or may be performed in multiple stages using a pair of rolls. The stretching ratio varies depending on the type of resin, but is usually preferably 2 to 15 times, and when the polyester composition of the present invention is used as one of the resins constituting the laminated polyester film, it is particularly preferably 2 to 7 times. In addition, the stretching temperature is preferably in the range of the glass transition temperature of the resin constituting the multi-layer laminated polyester film to the glass transition temperature + 100°C.
[0033] The uniaxially stretched film thus obtained may be subjected to a surface treatment such as corona treatment, frame treatment, or plasma treatment as necessary, and then may be imparted with properties such as easy slippage, easy adhesion, and antistatic properties by in-line coating.
[0034] The stretching in the width direction means stretching for giving the film a width direction orientation, and is usually performed by conveying the film while holding both ends with clips using a tenter to stretch it in the width direction. The stretching ratio varies depending on the type of resin, but is usually preferably 2 to 15 times, and when the polyester resin composition of the present invention is used as one of the resins constituting the laminated polyester film, it is particularly preferably 2 to 7 times. The stretching temperature is preferably in the range of the glass transition temperature of the resin constituting the multi-layer laminated polyester film to the glass transition temperature + 120°C.
[0035] The biaxially stretched film is preferably heat-treated in a tenter at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point in order to impart flatness and dimensional stability. By carrying out heat treatment, the dimensional stability of the film is improved. After being heat-treated in this manner, the film is uniformly cooled slowly, cooled to room temperature, and wound up. If necessary, a relaxation treatment or the like may be carried out in combination with the heat treatment and the slow cooling.
[0036] After being heat-treated in this manner, the sheet is gradually cooled uniformly, cooled to room temperature, and wound up.
[0037] In the multilayer laminated polyester film of the present invention having 100 or more layers laminated therein, the molar ratio of the naphthalenedicarboxylic acid component to the terephthalic acid component (naphthalenedicarboxylic acid component / terephthalic acid component) must be 0.85% or more as the composition of the entire multilayer laminated polyester film, and is preferably 0.90 or more from the viewpoint of reflection characteristics. The naphthalenedicarboxylic acid component is a component that greatly contributes to a high refractive index, and a high content of the naphthalenedicarboxylic acid component means that one of the polyester layers (polyester layer A) has a higher refractive index. A low content of the terephthalic acid component contributes to a low refractive index, and means that the refractive index of the other polyester layer (polyester layer B) is reduced. Therefore, an increase in the molar ratio of the naphthalenedicarboxylic acid component to the terephthalic acid component indicates that the refractive index difference between the high refractive index layer and the low refractive index layer is large, and optical characteristics such as reflection characteristics are improved. The laminated polyester film of the present invention is preferably used as a heat ray reflective polyester film that reflects infrared rays and the like. The polyester laminated polyester film of the present invention preferably contains a layer made of a polyester resin composition having a glass transition temperature of 100° C. or higher from the viewpoint of heat resistance. Furthermore, the glass transition temperature is preferably 110° C. or lower from the viewpoint of film formability. EXAMPLES
[0038] The present invention will be described in more detail below with reference to examples. The physical properties were measured and the effects were evaluated according to the following methods.
[0039] (1) Thermal properties of polyester resin compositions and films (glass transition temperature, crystallization temperature in the solid state) Approximately 10 mg of the sample to be measured was weighed out, sealed in an aluminum pan and pan cover, and measured using a differential scanning calorimeter (Q2000 type, manufactured by TA Instruments). In the measurement, the sample was heated to 300°C in a nitrogen atmosphere, held for 5 minutes, then removed and rapidly cooled to room temperature on an iron plate, and again heated from 20°C to 300°C at a rate of 16°C / min in a nitrogen atmosphere and held for 5 minutes. The midpoint glass transition temperature (the temperature at the point where the line equidistant in the vertical direction from the extended line of each baseline intersects with the curve of the step-like change part of the glass transition) when the temperature was raised at a rate of 16°C / min, and the peak temperature (crystallization temperature) due to crystallization observed when the temperature was raised at 16°C / min were measured. (2) Determination of the amount of alkali metal in the polymer Quantitative analysis was performed by atomic absorption spectrometry (polarized Zeeman atomic absorption spectrometer 180-80, Hitachi, Ltd.; flame: acetylene-air).
[0040] (3) Refractive index (optical property) The polyester resin composition was molten at 280°C in a vented twin-screw extruder, and then passed through a gear pump and a filter into a T-die to be molded into a sheet. The sheet was then rapidly cooled and solidified on a casting drum whose surface temperature was kept at 25°C by applying static electricity, to obtain an unstretched sheet having a thickness of 100 μm. The refractive index of the obtained unstretched sheet was measured according to JIS K7142 (1996) Method A.
[0041] (4) Solution haze (optical properties) 2 g of the polyester resin composition was dissolved in 20 mL of a 3 / 2 (volume ratio) mixed solution of orthochlorophenol / 1,1,2,2-tetrachloroethane, and the haze was measured by integrating sphere photoelectric photometry using a cell with an optical path length of 20 mm and a haze meter (HZ-1 manufactured by Suga Test Instruments Co., Ltd.). The solution haze is an index that indicates that the lower the value, the more excellent the transparency, and a value of 1.0% or less (◯, △) was considered to be acceptable.
[0042] 0.5% or less... ○ 0.6% or more and 1.0% or less △ Over 1.1%... ×
[0043] (5)ΔIV (heat resistance) 7 g of the polyester resin composition was weighed into a test tube and vacuum dried for 8 hours at 160° C. The dried polyester resin composition was melt-treated at 290° C. for 1 hour in a nitrogen atmosphere, and the difference between the intrinsic viscosity (IV) before drying and the intrinsic viscosity after the melt-treatment was calculated as ΔIV. The intrinsic viscosity (IV) was measured at 25°C by preparing a calibration curve according to JIS K7367-5:2000 (ISO 1628-5:1998) and dissolving 0.1 g of polymer in 10 ml of o-chlorophenol at 160°C for 20 minutes. The smaller the difference in ΔIV, the better the heat resistance during melting. A ΔIV of 0.5 or less was considered acceptable. 0.30 or less... ○ 0.31 or more and 0.50 or less △ 0.51 or above... ×
[0044] (6) Measurement of naphthalenedicarboxylic acid and terephthalic acid in film The contents of naphthalenedicarboxylic acid and terephthalic acid in the multi-layer laminate polyester film were determined by NMR. After sampling the multi-layer laminate polyester film, it was dissolved in hexafluoroisopropanol (HFIP) / d2 chloroform (volume ratio 1 / 1) and quantified using 1H-NMR. After quantification, the molar ratio of naphthalenedicarboxylic acid and terephthalic acid (naphthalenedicarboxylic acid / terephthalic acid) was calculated.
[0045] (7) Measurement of heat loss Using a Seiko Instruments TG / DTA6200, the temperature was raised from room temperature to 300°C at a rate of 20°C / min under a nitrogen flow (50 ml / min). The weight at which the sample reached 300°C was used as the reference weight, and the difference in weight after 150 minutes at 300°C was calculated as the thermal loss.
[0046] The point at which 300° C. is reached is set as the zero point in order to cancel the influence of low-boiling oligomer components and moisture in the polyester resin composition, which are usually removed in the drying step. Resins dried at 180°C for more than 3 hours under reduced pressure in a vacuum dryer were used for measurement using a Shimadzu Flow Tester CFT-500A manufactured by Shimadzu Corporation. The amount of resin was set to approximately 5g, and the melting temperature was set to 270°C. Loads were set to 10N, 20N, and 50N (loading started 5 minutes after sample setting began), and the shear rate and melt viscosity were determined at each load. The die was φ1mm, L=10mm. Measurements were performed three times for each load, and the average values were calculated, and the melt viscosity and shear rate data obtained at each load were graphed, and the value at a shear rate of 100 (1 / sec) was determined from the graph.
[0047] (8) Reflectance (optical properties) A laminated polyester film cut to 5cm x 5cm was used to measure the reflectance and transmittance using a Hitachi spectrophotometer (U-4100 Spectrophotometer) with an integrating sphere attached to the basic configuration. Reflectance measurements were performed using the aluminum oxide secondary white plate attached to the device as a reference. For reflectance measurements, the sample was placed behind the integrating sphere with its longitudinal direction facing up and down. For transmittance measurements, the sample was placed in front of the integrating sphere with its longitudinal direction facing up and down. Measurement conditions: The slit was set to 2nm (visible) / automatic control (infrared), the gain was set to 2, and the scan speed was measured at 600nm / min to obtain the reflectance at an azimuth angle of 0 degrees.
[0048] (9) Film forming properties The film formability was judged based on the presence or absence of flow marks in the obtained laminated polyester film, and films with no visually observed flow marks were rated as acceptable.
[0049] Example 1 95.5 parts by weight of dimethyl naphthalenedicarboxylate, 47.6 parts by weight of ethylene glycol, and 9.2 parts by weight of polyethylene glycol (number average molecular weight 400) were charged into a reaction vessel and dissolved at 180°C, and then 0.055 parts by weight of manganese acetate tetrahydrate and 0.015 parts by weight of antimony trioxide were added while stirring to start the transesterification reaction. The temperature was raised to 235°C while distilling off methanol over 3.5 hours, and the transesterification reaction was completed. 0.022 parts by weight of phosphoric acid, 0.026 parts by weight of sodium dihydrogen phosphate dihydrate, and 0.1 parts by weight of IRGANOX1010 were added, and the excess ethylene glycol was distilled off.
[0050] The reaction product was transferred to a polycondensation reaction vessel, and while heating from 240° C., the pressure was reduced to 133 Pa or less, and while distilling off the excess ethylene glycol, the temperature was raised to 290° C. When the desired melt viscosity was reached, the product was discharged into a water tank and cut into chips using a strand cutter.
[0051] The resulting polyester composition had a heat loss of 0.09% by weight, a glass transition temperature (Tg) of 101° C., a crystallization temperature (Tc) from the solid state of 216° C., and a solution haze of 0.2%.
[0052] The obtained polyester composition (hereinafter referred to as polyester A) and a non-crystalline (no melting point) PET resin (hereinafter referred to as polyester B) having a glass transition temperature of 79°C and copolymerized with 30 mol% of cyclohexane dimethanol with respect to the total diol components were each melted at 280°C in a vented twin-screw extruder, and then merged in a 201-layer feed block through a gear pump and a filter. Both surface layers of the laminated polyester film were polyester A, and the layer thickness of the B layer mainly composed of polyester B adjacent to the A layer mainly composed of polyester A was made to be almost the same. After being merged in the 201-layer feed block, the mixture was introduced into a T-die and formed into a sheet, and then rapidly cooled and solidified on a casting drum whose surface temperature was kept at 25°C by applying electrostatic force to obtain a cast film. The discharge amount was adjusted so that the weight ratio of polyester A to polyester B was about 1:1, and the thickness ratio of adjacent layers was about 1.
[0053] The obtained cast film was heated with a group of rolls set at a temperature 10°C higher than the glass transition temperature of Polyester A, and then stretched 4.0 times in the longitudinal direction while being rapidly heated from both sides of the film with a radiation heater within a stretching section length of 100 mm, and then cooled once. The uniaxially stretched film was then introduced into a tenter, preheated with hot air at 100°C, and stretched 4.0 times in the transverse direction at a uniform stretching speed at a temperature of 20°C above the glass transition temperature of Polyester A. The stretched film was then heat-treated in the tenter with hot air at 235°C, and then relaxed by 2% in the transverse direction at the same temperature. It was then gradually cooled to room temperature and wound up. The thickness of the resulting laminated polyester film was 40μm.
[0054] The obtained laminated polyester film had no flow marks, was excellent in transparency, had low reflectance in the visible light region (400 to 800 nm) and high reflectance in the infrared region (900 to 1200 nm), and was applicable as a heat ray reflecting film. The results are shown in Table 1.
[0055] The glass transition temperature and heat of crystalline fusion of the film were measured by scraping off the surface layer (polyester A layer) as a sample according to (1) Method for measuring thermal properties of polyester composition and film.
[0056] Examples 2 to 7, Comparative Examples 1 and 2 (Examples 2 and 3 (Read as Reference Examples 1 and 2) Amount of polyethylene glycol added and molecular weight, content of alkali metal elements, alkali metal The polyester composition and the stacked polymer were prepared in the same manner as in Example 1, except that the type of the metal compound was changed. A multi-layer polyester film was obtained. The evaluation results are shown in Tables 1 and 2.
[0057] In Example 2, when the amount of PEG400 and the amount of alkali metal compound added were increased, the glass temperature decreased, the heat loss increased, and the solution haze tended to increase, but these were within the scope of claim 1 of the present invention and the performance was not problematic as a heat ray reflective film.
[0058] In Example 3, when the amount of PEG400 added was reduced, the thermal loss decreased, the glass transition temperature increased, and flow marks occurred during film formation. However, this was within the scope of claim 1 of the present invention, and the performance was not problematic as a heat ray reflective film.
[0059] In Example 4, when the amount of PEG200 was changed and the amount of alkali metal compound added was reduced, Tg tended to increase and Tc tended to decrease, but this was within the scope of claim 1 of the present invention and the performance was not problematic as a heat ray reflective film.
[0060] In Example 5, when PEG600 was used and the amount of alkali metal compound added was increased, the solution haze tended to increase, but this was within the scope of claim 1 of the present invention and the performance was not problematic as a heat ray reflective film.
[0061] In Example 6, when the amount of alkali metal compound added was changed to "0," the heat resistance (ΔIV) tended to decrease, but this was within the scope of claim 1 of the present invention and the performance was not problematic as a heat ray reflective film.
[0062] In Example 7, when the amount of alkali metal compound added was increased, the solution haze tended to increase, but this was within the range of claim 1 of the present invention and the performance was not problematic as a heat ray reflective film.
[0063] In Comparative Example 1, when the amount of PEG400 added was increased, the thermal loss was 0.57% by weight, and the effect of suppressing pyrolysis gas was insufficient.
[0064] In Comparative Example 2, when PEG1000 was used, the thermal loss was 0.31% by weight, and the effect of suppressing pyrolysis gas was insufficient.
[0065] Comparative Example 3 A polyester resin composition and a laminated polyester film were obtained in the same manner as in Example 1, except that dimethyl naphthalenedicarboxylate was 87.7 parts by weight, dimethyl terephthalate was 7.7 parts by weight, and polyethylene glycol (number average molecular weight 400) was 6.4 parts by weight. The results are shown in Table 2. The obtained polyester resin composition had a thermal loss of 0.33% by weight, and the thermal decomposition gas suppression effect was insufficient.
[0066] Example 8 A polyester resin composition and a laminated polyester film were obtained in the same manner as in Example 1, except that 92.9 parts by weight of dimethyl naphthalenedicarboxylate, 3.9 parts by weight of dimethyl terephthalate, and 4.8 parts by weight of polyethylene glycol (number average molecular weight 400) were used. The results are shown in Table 1. The obtained polyester resin composition had a tendency to have a lower refractive index and an increased thermal loss, but this was within the range of claim 1 of the present invention, and the performance was satisfactory as a heat ray reflective film.
[0067] Example 9 A polyester resin composition and a laminated polyester film were obtained in the same manner as in Example 1, except that dimethyl naphthalenedicarboxylate was 95.3 parts by weight, p-xylene glycol was 2.7 parts by weight, and polyethylene glycol (number average molecular weight 400) was 4.7 parts by weight. The results are shown in Table 1. The obtained polyester resin composition tended to have an increased heat loss, but this was within the range of claim 1 of the present invention, and the performance was satisfactory as a heat ray reflective film.
[0068] [Table 1]
[0069] [Table 2]
Claims
1. 1. A polyester resin composition comprising an aromatic dicarboxylic acid unit and an alkylene glycol unit, the polyester resin composition having a naphthalene dicarboxylic acid component content of 95 mol % or more relative to all dicarboxylic acid components, an ethylene glycol component content of 95 mol % or more relative to all diol components, and a polyalkylene glycol component, the polyester resin composition having a heat loss of 0.3 wt % or less when heated at 300°C for 150 minutes in a nitrogen atmosphere, a glass transition temperature of 100°C or more and 110°C or less as measured by differential scanning calorimetry, and a crystallization temperature in the solid state of 200°C or more and 220°C or less.
2. 2. The polyester resin composition according to claim 1, wherein the content of the alkali metal element is from 10 ppm to 100 ppm based on the mass of the polyester resin composition.
3. 3. The polyester resin composition according to claim 2, wherein the compound containing an alkali metal is an alkali metal phosphate.
4. 4. The polyester resin composition according to claim 1, wherein the polyalkylene glycol is polyethylene glycol and has a number average molecular weight of 200 or more and 600 or less.
5. The polyester resin composition according to claim 4, wherein the content of the polyethylene glycol is 4% by weight or more and 8% by weight or less based on the mass of the polyester resin composition.
6. A polyester film comprising 80% by weight or more of the polyester resin composition according to any one of claims 1 to 5.
7. 7. A laminated polyester film comprising at least one layer of the polyester film according to claim 6, the laminated polyester film having a highest glass transition temperature of 100° C. or higher as measured by differential scanning calorimetry.
8. 8. The multi-layer laminated polyester film according to claim 7, wherein the number of layers is 50 or more.
9. A heat ray reflective polyester film comprising the laminated polyester film according to claim 7 or 8.
10. 9. The multi-layer laminate polyester film according to claim 8, wherein the number of layers is 100 or more, and the molar ratio of the naphthalene dicarboxylic acid component to the terephthalic acid component (naphthalene dicarboxylic acid component / terephthalic acid component) of the entire multi-layer laminate polyester film is 0.86 or more.
Citation Information
Patent Citations
Polyethylene naphthalate resin
JP1996048758A
Polyethylene naphthalate resin
JP1996048759A
Multilayer optical film
JP2006205729A
Copolyester, and polyester fiber with excellent moisture absorbency including the same
JP2013087153A
Uniaxially oriented multilayer laminate film and optical member comprising the same
JP2016024313A